KARAKTERISTIK PATI DARI BATANG POHON AREN PADA BERBAGAI FASE PERTUMBUHAN - Nur Alam Nur Alam; Muhammad Salim Saleh (Universitas Tadulako, 2009)
The aims of this experiment were to determine the most suitable phase of palm sugar tree for producing starch and the characteristics of starch (functional, physical and chemical compositions) which were appropriate for starch noodle. Three growth phases of palm sugar tree were observed, namely: before flowering, productive growth and post growth productive phases. Starch characteristics analyzed included water content, reduced sugar, starch, amylase, lipid, protein, fiber, ash, acid degree, form and size of granular, and starch amilography. Starch of green bean was used as a comparison. Results of this experiment indicated that the highest starch content on the palm sugar tree was found at the productive growth phase. The characteristics of starch on the palm sugar at the post growth productive phase were similar to the starch of green bean. Therefore, starch obtained from post growth productive phase is the best for starch noodle.